Next-Generation Business Intelligence Software with Silverlight 3 - Czernickiva, Bart (Apress, 2012)
It is a very exciting time to be in the software development industry. The governing concepts of developing software are changing and rapidly evolving before our eyes. Skills and frameworks that you may have used even just two years ago could very well be considered obsolete and replaced with something more efficient. This is why software vendors and the developers of engineering products need to stay on top of emerging technology concepts in order to remain competitive. Two technologies that are experiencing exponential growth and are quickly becoming in demand are business intelligence (BI) and rich interactive applications (RIAs). Knowing how to use and implement either of these technologies will be vital in order to develop modern-looking applications in the near future. More importantly, learning how to use BI concepts and bringing them to life with RIA technology will allow you to deliver superior software that is a cut above the competition. The first core technology this book focuses on is BI. BI can be simply defined as delivering key insight quickly from large data repositories. This information can be presented in the form of reports, charts, analytical aggregates, data grids, and so on. Until recently, BI deployments have not been cheap and often required expensive hardware and enterprise-scale software to perform complex data calculations. Furthermore, the tools that presented BI information were geared for people with a background in number crunching (statistical analytics). This really limited the scope of BI because in order to use BI tools, you had to have a good understanding of the numbers you were looking at in order to analyze them properly. BI technology’s steep learning curve limits its adoption to larger enterprise organizations. Just like any other technology, BI is maturing as a platform and adopting new concepts from emerging software development methodologies.ÿÿÿÿÿ